Citrus aurantium L. and synephrine improve brown adipose tissue function in adolescent mice programmed by early postnatal overfeeding - Guimarães, Andressa Cardoso; de Moura, Egberto Gaspar; Silva, Stephanie Giannini; Lopes, Bruna Pereira; Bertasso, Iala Milene; Pietrobon, Carla Bruna; Quitete, Fernanda Torres; de Oliveira Malafaia, Tayanne; Souza, Érica Patrícia Garcia; Lisboa, Patrícia Cristina; de Oliveira, Elaine (Frontiers in Nutrition, 2024)
Obesity is a multifactorial condition with high health risk, associated with important chronic disorders such as diabetes, dyslipidemia, and cardiovascular dysfunction. Citrus aurantium L. (C. aurantium) is a medicinal plant, and its active component, synephrine, a β-3 adrenergic agonist, can be used for weight loss. We investigated the effects of C. aurantium and synephrine in obese adolescent mice programmed by early postnatal overfeeding. Three days after birth, male Swiss mice were divided into a small litter (SL) group (3 pups) and a normal litter (NL) group (9 pups). At 30 days old, SL and NL mice were treated with C. aurantium standardized to 6% synephrine, C. aurantium with 30% synephrine, isolated synephrine, or vehicle for 19 days. The SL group had a higher body weight than the NL group. Heart rate and blood pressure were not elevated. The SL group had hyperleptinemia and central obesity that were normalized by C. aurantium and synephrine. In brown adipose tissue, the SL group showed a higher lipid droplet sectional area, less nuclei, a reduction in thermogenesis markers related to thermogenesis (UCP-1, PRDM16, PGC-1α and PPARγ), and mitochondrial disfunction. C. aurantium and synephrine treatment normalized these parameters. Our data indicates that the treatment with C. aurantium and synephrine could be a promising alternative for the control of some obesity dysfunction, such as improvement of brown adipose tissue dysfunction and leptinemia.